Education, Disappointment and Optimal Policy - Dan Anderberg; Claudia Cerrone (Center for Economic Studies and ifo Institute (CESifo), 2014)
Justification for policies to encourage investments in education, particularly for individuals at the lower end of the ability distribution, may be provided by behavioural economics. We present a prototypical model where individuals who are potentially loss averse around their expected outcome make risky investments in education and we draw on optimal tax theory to explore the design of policy. The model highlights the critical roles played by (i) the relationship between behavioural risk preferences, standard risk aversion and labour supply behaviour, (ii) the risk properties of education, and (iii) the degree of observability of individual academic ability.
Keywords: D81; H21; I21; 330; education; risk; disappointment; optimal taxation